Addressing Metabolic Syndrome In Family Practice: Screening Tools And Lifestyle Interventions (The Review of Diabetic Studies, 2025)
Background: Metabolic syndrome is a cluster of interrelated risk factors: central obesity, hypertension, dyslipidemia, and hyperglycemia that when present together raises the risk of cardiovascular disease and type 2 diabetes. There has been a global rise in the prevalence of metabolic syndrome running parallel to the rise in obesity. A broader impact on health is linked with metabolic syndrome as it has also been associated with other comorbidities like fatty liver, polycystic ovarian disease and certain cancers. Objective: This review aims at addressing metabolic syndrome in family practice with detailed review of screening tools and lifestyle interventions.Methodology: The review is comprehensive research of PUBMED and Google scholar from the year 2001 to 2024.Conclusion: Clustering of various modifiable risk factors which when presented together pose a serious threat to health is termed as metabolic syndrome. Metabolic syndrome is screened by setting certain guidelines for obesity, blood pressure and other risk factors and adhering to the standard target ranges. Lifestyle modification is the mainstay for management of metabolic syndrome. Treating the risk factors individually by modifying lifestyle plays an important role in the management of metabolic syndrome. All the risk factors should be treated simultaneously. Lifestyle modification has proven to reverse metabolic syndrome if implemented on time.  A multidisciplinary, team-based care model involving dietitians, exercise specialists, diabetes educators, and sometimes endocrinologists or cardiologists can enhance support for the patient and improve adherence.